Cong nghiep hoa nong nghiep va phat trien nong thon Agricultural industrialization and rural development - Ngo, Xuan Binh.; Xiao, Xinhuang; Vien nghien cu ong Bac A (Vietnam).; hong yang yan jiu yuan. Ya tai qu yu yan jiu zhuan ti zhong xin. (Hanoi Nha xuat ban Khoa hoc t nhien va cong nghe, 2008)
Papers on analysis and assessments of achievement, impacts, challenges of industrialization and international integration to agricultures in Taiwan and Vietnam.
At head of title: Vien nghien cu ong Bac A, Center for Asia-Pacific Area Studies, RCHSS, Academia Sinica.
"2nd bilateral international worshop was organized in Hanoi, Dec. 22, 2007.--P. xi
In English and Vietnamese.
Keywords: Agriculture -- Economic aspects -- Vietnam -- Congresses; Agricultural innovations -- Vietnam -- Congresses; Rural development -- Vietnam -- Congresses; Agriculture -- Economic aspects -- Taiwan -- Congresses; Agricultural innovations -- Taiwan -- Congresses; Rural development -- Taiwan -- Congresses